Find A + B given that A and B are constants such that
x 2 − x − 6 2 x − 9 = x − 3 A + x + 2 B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You can actually just see that since X is not a constant in this problem, the x value on both sides must be equal, so A x + B x = 2 x , ( A + B ) = 2 . This is basically what you did, just a little quicker!
x 2 − x − 6 2 x − 9 = ( x − 3 ) A + ( x + 2 ) B = > 2 x − 9 = A ( x + 2 ) + B ( x − 3 ) . . . . . . . . . . . . . . . . . . ( i ) P u t t x = 3 i n ( i ) 2 ( 3 ) − 9 = A [ ( 3 ) + 2 ] + B [ ( 3 ) − 3 ] o r 6 − 9 = 5 A + 0 o r − 3 = 5 A = > A = − 5 3 N o w P u t t x = − 2 i n ( i ) 2 ( − 2 ) − 9 = A [ ( − 2 ) + 2 ] + B [ ( − 2 ) − 3 ] o r − 4 − 9 = 0 − 5 B o r − 1 3 = − 5 B = > B = 5 1 3 N o w " A + B " A + B = − 5 3 + 5 1 3 = 5 − 3 + 1 3 = 5 1 0 o r A + B = 2
Did it the same way.
Problem Loading...
Note Loading...
Set Loading...
Simple.
x 2 − x − 6 = ( x − 3 ) ( x + 2 )
This can make the question easier to solve.
x 2 − x − 6 2 x − 9 = x − 3 A + x + 2 B
x 2 − x − 6 2 x − 9 = x 2 − x − 6 A ( x + 2 ) + x 2 − x − 6 B ( x − 3 )
2 x − 9 = A x + 2 A + B x − 3 A
This equation can be transferred into 2 equations:
2 x = A x + B x . . . ( 1 )
− 9 = 2 A − 3 B . . . ( 2 )
From the first equation, it is clear that the answer can be derived from it. Dividing both sides by x yields
2 = A + B
Hence, our answer is 2.